Teknik Pernapasan terhadap Dispnea pada Pasien PPOK - Rahmi Rahmi; Dewi Irawati; Agung Waluyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine breathing techniques that can be used to reduce dyspnea in COPD patients. The method used is to search articles on several electronic databases, namely Proquest, ScienceDirect, PubMed, Embase, and EBSCOHost, using the keywords Breathing Technique, Dyspnea, and COPD. Inclusion criteria were COPD patients, articles with RCT or clinical trial research designs published in the last ten years, and interventions that included breathing techniques. The results showed that several breathing techniques could reduce dyspnea in COPD patients, including pursed lip breathing, active cycle breathing, breathing control, deep breathing, and yoga. In conclusion, these breathing techniques can be used in COPD patients. Breathing techniques can reduce dyspnea and improve quality of life, sputum discharge, lung capacity, and anxiety. Keywords: Breathing Technique, COPD, Dyspnea